ANALISIS JARAK ANTARA DUA KANAL YANG BERBEDA YANG SALING BERDEKATAN PADA SATU BTS BERSAMA - Abdul Samad Prayudi . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2017)
The  different  space  of  joint  BTS  would  potentially  create  interference  which could interfere the performance quality of an operator. Isolation denoted a value from each antenna which had common value of 30 dB. This minimum spacing calculation was used according to space isolation calculation. In case of frequency of 1710 up to 2170 Mhz, it was obtained that the minimum vertical spacing was 0.15 up to 0.19 meter, for frequency of 1710 up to 2170 Mhz, it was obtained that the minimum horizontal spacing was 0.63 up to 0.82 meter, for slant spacing obtained with isolation value was 71.436 dB. Spacing installation at BTS PAL 5 Jln   Husin   Hamsah,   RT/RW   005/001,   Kelurahan   Paal   Lima,   Kecamatan Pontianak  Barat  was  4.5  meter  for  vertical  spacing,  2  meter  for  horizontal spacing, and 71.436 dB which was more than 30 dB for slant isolation. Thus, the result obtained in the field showed antenna spacing at BTS PAL 5 Barat had met the standard for antenna isolation. Antenna with isolation value of <30 dB had to be adjusted toward installed antenna; extent spacing between one antenna to the others;  adjust tilt  of antenna in order to  increase isolation  value of antenna; adjust azimuth angle by getting it away from antenna that had been interfered so that the isolation value of the antenna met the standard. The receiving level of MS also had to be taken into account to measure the power of receiving signal of each MS from installed antenna, with Walfish-Ikegami method, it was obtained that the value of receiving power decreased upon spacing of 1km from antenna, so that there should be certain adjustments toward the height of the antenna.     Key Words: Antenna isolation, space isolatioan calculation, joint BTS, quality of signal